2011
DOI: 10.1063/1.3669701
|View full text |Cite
|
Sign up to set email alerts
|

Contact effects in high performance fully printed p-channel organic thin film transistors

Abstract: Contact effects have been investigated in fully printed p-channel organic thin film transistors with field effect mobility up to 2 cm2/Vs. Electrical characteristics of the organic thin film transistors, with channel length <200lm, are seriously influenced by contact effects with an anomalous increase of the contact resistance for increasing source-drain voltage. Assuming that contact effects are negligible in long channel transistors and using gradual channel approximation, we evaluated the current-voltage ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 13 publications
4
64
0
Order By: Relevance
“…This is evident from the output characteristics shown in Fig. 6 and, according to several studies [51,52,53,54], we verified that it is due to the parasitic contact resistance at the source injecting contact. This is further confirmed by the normalized transfer characteristics shown in Fig.…”
Section: Resultssupporting
confidence: 48%
“…This is evident from the output characteristics shown in Fig. 6 and, according to several studies [51,52,53,54], we verified that it is due to the parasitic contact resistance at the source injecting contact. This is further confirmed by the normalized transfer characteristics shown in Fig.…”
Section: Resultssupporting
confidence: 48%
“…Thus, at high electric field, the barrier in this region of the source can be modulated, and since the reverse current of the contact is exponentially dependent on effective barrier height 20 , large changes in current (I 1 ) can be effected by changing the potential on the gate. The drain bias, however, has a similar effect on this area of the source, so without purposeful screening of the source edge from drain electric field 11 , output characteristics have a drain voltage dependence of the current in saturation 5,9 .…”
Section: A Modes Of Operation and Source Geometrymentioning
confidence: 99%
“…Regardless of the current injection mechanism at the source 3,5,6 , the intentional use of a source barrier in an otherwise conventional TFT structure leads to major differences in the transistor (output) characteristic: low-voltage saturation 2,3,[7][8][9][10] , flat saturated output characteristics 3,7,9,11 , tolerance to geometrical variations 4,12 , bias stress stability 13 and improved current levels in low mobility materials 14 . Both digital 15 and analog applications 14,[16][17][18][19] could benefit from using these devices, in terms of amplification, energy efficiency, uniformity of electrical performance, and reliability.…”
Section: A Schottky Barrier Source-gated Transistors (Sb-sgts)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the model in [21] tends to overestimate the drain current due to contact effects. For this reason, the contact model described in [23] has been added to the simulation model, and its parameters have been In order to model the electrical characteristics of double gate TFTs, an approach similar to [24] has been followed. It has been observed that the TG bias modifies the transfer curves in two ways: a threshold modulation for negative TG bias, and a modulation of the on-current for positive TG bias.…”
Section: B Channel Current Modellingmentioning
confidence: 99%